2010
DOI: 10.1179/174328409x448493
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of boundary migration during grain growth in fully recrystallised high purity nickel

Abstract: The movement of individual boundaries during grain growth after primary recrystallisation in a 96% cold rolled sample of pure nickel has been followed using electron backscatter diffraction maps of the same surface area taken after each of several annealing steps. Particular attention is given to the migration of boundaries with near Σ3 misorientations. During annealing, a small reduction in the length fraction the Σ3 boundaries was observed in the early stages of annealing. Analysis of individual boundaries s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 27 publications
(31 reference statements)
0
3
0
Order By: Relevance
“…Even more frequently, an EBSD map has to be compared with other EBSD maps of the same series collected during in-situ and ex-situ experiments [18][19][20][21][22][23]. In these cases, the coordinates in each of the EBSD map can be distorted relatively to the others because non-constant drift typically leads to different distortion among the series.…”
Section: Introductionmentioning
confidence: 99%
“…Even more frequently, an EBSD map has to be compared with other EBSD maps of the same series collected during in-situ and ex-situ experiments [18][19][20][21][22][23]. In these cases, the coordinates in each of the EBSD map can be distorted relatively to the others because non-constant drift typically leads to different distortion among the series.…”
Section: Introductionmentioning
confidence: 99%
“…However, with increasing annealing time the recrystallized cube-oriented grains do not have a size advantage in comparison with the noncube-oriented grains nucleated at the initial stage. Previously, several literatures [6,25,26] demonstrated that the size advantage of cube-oriented grains was attributed to the higher growth rate for the cube-oriented grains misoriented 40~60 ∘ with surrounded matrix about <111> axis in the unidirectionally rolled specimens. Lin et al [26] demonstrated that the higher growth rate for super-cube oriented grains was related to the preferential growth into S-oriented matrix.…”
Section: Microstructure Evolution During In-situ Annealing In the Ccrmentioning
confidence: 99%
“…In other words, the cubeoriented grains grow faster than other grains due to its special relationship with the surrounding deformed matrix [1]. It has been demonstrated that the boundaries with a misorientation angle of 40~60 ∘ around <111> axis have a higher migration rate during recrystallization [6]. That is to say, the oriented growth mechanism emphasizes the importance of the misorientation environments around the cube-oriented regions for the formation of sharp cube texture.…”
Section: Introductionmentioning
confidence: 99%